SEMIOTIKA LIRIK LAGU DALAM ALBUM LELAKU-FOURTWNTY KARYA ARI LESMANA (KAJIAN SEMIOTIKA) - Sujoko Sujoko; Hafidz Erdinal Arrazy (Universitas Batanghari, 2019)
The purpose of this research is to describe the semiotic of Lelaku Fourtwnty’s song lyric by Ari Lesmana. This research is descriptive qualitative. The primary data is in the form of lines which consist of semiotic icon and symbol in the song lyric of Lelaku Fourtwnty. The technique used in collecting the data is by using library study which focuses on analyzing semiotic icon and symbol in the lyric. The result of the analysis which is acquired from the song lyric of Fourtwnty by Ari Lesmana are; there are 4 icons and 2 symbols in the aspect of mild irritation, there are 4 icons and 3 symbols in the aspect of nature poem; there are 4 icons and 2 symbols in the aspect of black and white; there are 3 icons and 4 symbols in the aspect of pink blurry; there are 2 icons and 2 symbols in the aspect of self-calm; there are 2 icons and 2 symbols in the aspect of I am not an animal; there are 3 icons and 3 symbols in the aspect of tacit; there are 2 icons and 2 symbols in the aspect of dimension argumentation; and there are 3 icons and 2 symbols in the aspect of dawn discussion. Keywords: Analysis, Icon and Symbol, Song Lyric